Phylogeny and aspects of reproductive biology of aridarum (Schismatoglottideae: Araceae) - Shook Ling, Low (Universiti Malaysia Sarawak (UNIMAS), 2015)
Aridarum Ridl., a genus of wholly rheophytes, is traditionally defined by its petiolar sheathextended intoafree ligularportion,notconstricted spathe, truncatestamenswithan excavated (not always) top and a pair of horn thecae, and infructescence with a cluster of berries subtended by obconic persistent lower spathe. Aridarum is further divided into two sections, sect. Aridarum and sect. Caulescentia based on primarily the position of the thecae horns. Recent discoveries of 16 novel species resulted in 400% increase in species number for the genus, making it to 25 published species. Therefore, this study was carried out to: (1) investigate the phylogenetic signals among Aridarum species; (2) examine the flowering behavior and its related floral microstructures of several selected Aridarum species; (3) determine the pollination strategies of A. nicolsonii Bogner, A. caulescens M.Hotta and A. velutandrum S.Y.Wong, S.L.Low & P.C.Boyce in its natural habitat; (4) link the floral traits of several selected Aridarum species to its pollination strategies.